Lyde Green Roman Villa, Emersons Green, South Gloucestershire - Hobson, Matthew S. (Archaeopress Publishing, 2021)
"Lyde Green Roman Villa, Emersons Green, South Gloucestershire was excavated between mid-2012 and mid-2013 along with its surroundings and antecedent settlement. The excavations took place as part of the Emersons Green East Development Area, funded through the mechanism of commercial archaeology by Gardiner & Theobald LLP. The results of the stratigraphic analysis are given here along with specialist reports on the human remains, pottery (including thin sections), ceramic building material, small finds, coinage and iron-working waste. Six open-area excavations allowed the archaeologists the rare opportunity to trace a substantial part of the site's layout. Three ancillary buildings within the villa compound, including a bathhouse, were excavated. Evidence of advanced water management was uncovered in the form of lead piping, ceramic drain tiles and an enigmatic stone structure built into a canalised spring line. The villa's economy included stock raising, crop processing and iron and textile production. The settlement appears to have originated in the mid-1st century AD, or slightly earlier. "